Evaluation of the Potential of Renewable Thermal Energy from Shingles Using Thermoelectric Generator (TEG) for Residential Use Application - Wan Jamaludin, Wan Akashah; Johar, Muhammad Akmal; Marwah, Omar Mohd Faizan; Mohd Amin, Azriszul (Penerbit Akademia Baru, 2020)
A thermoelectric generator (TEG) using Seebeck effect to generate electrical energy in a residential application encompasses a case study of a test rig consisting of a concrete shingle as case study material. This paper explores its behavior and response to changes in temperature throughout the day. Four TEGs in series are mounted on the underside of a shingle. The measurement of the voltage and current response were made to determine the power generated. Using National Instruments as a data acquisition device with thermocouple probes to gather all the necessary data of which are discussed in the paper. From the experiments, the modules were able to generate up to 65.22 μW at 138Ω. This shows a considerable potential of TEG application in residential areas, as they are scalable.